Internalisasi Nilai Pancasila dalam Pembentukan Sikap Anti-Korupsi Siswa SMA - Kournukova Pardede, Christien Yunike; Sianturi, Ester Enjelika; Ananda, Gracia; Ritonga, Levi; Rizky, Reny Nadia; Sembiring, Sindi Novelia Br; Setiawan, Anugerah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the internalization of Pancasila values in shaping students’ anti-corruption attitudes at SMA HKBP Sidorame Medan. This descriptive qualitative research employed observations, interviews, and documentation, with data analyzed through reduction, display, and conclusion drawing. The findings show that the internalization of values is carried out through PPKn learning, school habituation, teacher exemplification, and extracurricular activities. Values such as honesty, responsibility, discipline, deliberation, and justice are integrated into school activities. The internalization of Pancasila values has been shown to shape students’ anti-corruption attitudes, reflected in their avoidance of cheating, compliance with school regulations, and courage to reject unethical behaviors. Supporting factors include school commitment, teacher role modeling, extracurricular involvement, and family support. Inhibiting factors include peer influence, low awareness, and misuse of technology. Overall, Pancasila plays a significant role in strengthening students’ integrity-based character.